(untitled) (Hematology Meeting Reports, 2009)
The neonate is born with a combined deficiency in plasma coagulation factors, natural inhibitors of haemostasis and components of the fibrinolytic system. In the healthy neonate, there is a balance between haemostatic systems, therefore under normal circumstances, the healthy neonate does not present haemorrhage or thrombosis. However several coagulation disorders, congenital or acquired, may be expressed during the neonatal period in a healthy or diseased neonate. Haemophilia A, B (Haem-A, B) and von Willebrand disease (vWD) are the most common inherited coagulation disorders, whereas congenital deficiencies of FI, FII, FV, FVII, FX, FXI, FXII or FXIII occur rarely. Cephalematoma, intracranial haemorrhage (ICH), bleeding from the umbilicus cord may be the first signs of congenital FXIII, FVII or FVIII deficiency. Acquired coagulation plasma factors deficiency is usually associated with vitamin K deficiency (early, classic, late haemorrhagic disease, secondary haemorrhagic disease), liver insufficiency (hepatitis, metabolic diseases e.t.c) or disseminated intravascular coagulation, complicating severe sepsis. Platelets are produced from the 11th gestational week of the foetus. The healthy neonate, full-term or premature, is born with a normal platelet value (>150x109/L). Any value